An analysis on the impact of social networks on corporate image: evidence from Turkey - Fakıoğlu, Mehmet Tarık (My University, 2019)
Sosyal ağlar, kurumların en fazla kullandığı iletişim kanalları arasındadır. Sosyal ağlar sayesinde; işletmeler kolay, sürekli ve ekonomik bir şekilde kendi kurum profillerini yaratabiliyorlar; online müşteri ilişkileri, ürün/ hizmet bilgileri ve özel teklifler sunabiliyorlar. Kurumsal sosyal medya faaliyetleri aracılığıyla kurumlar ile paydaşları (müşterileri dahil) arasındaki sınırlar azalmakta ve etkileşim gerçek-zamanlı hale gelmektedir.Kurumlar, günümüzün rekabetçi ortamında, kurum ile çevresi arasında uzun vadeli ilişki kurabilmek için pozitif kurum imajının ne derece önemli olduğunun farkındalar. Güçlü bir kurum imajı kuruma duygusal bir değer katacak; kurumu ayırt edilebilir ve inanılır kılacak, bu da kurumun rakipleri karşısında öne geçmesini sağlayacaktır.Sosyal ağların kurum imajına etkisini belirlemek için her iki kavramın boyutları belirlenmiştir. Bir anket formu kullanılarak, sosyal ağ faaliyetlerinin algılanan önem düzeyleri araştırılmış ve sosyal ağları aktif olarak kullanan kurumların algılanan imajları ölçülmüştür. Araştırmanın sonuçları; kurumların, kurum imajlarına olumlu yönde etki etmek için sosyal ağları aktif olarak kullanmaları gerektiğini göstermiştir. Kurum imajlarını artırmaları ve sektör lideri yenilikçi kurumlar olarak görülmeleri için; kurumların kullanıcılarla aktif olarak etkileşmeleri ve bir kullanıcının ihtiyaç duyabileceği tüm bilgileri sosyal ağ faaliyetlerinde sağlamaları şarttır.

Social networks are among the most common channels of communication that corporations use. Thanks to social networks; businesses can simply, continuously and economically create their own corporate profiles and initiate online customer service, product/ service information and special offerings. With corporate social media activities, the boundaries between corporations and its stakeholders (including its customers) diminish and interaction becomes real-time.In today’s competitive environment, corporations are aware that creating a positive corporate image is key in establishing long-term relationships between the corporation and its surroundings. A strong corporate image will add emotional value to the corporation; make them distinguishable and believable, which in turn will enable the corporation to get ahead of its competitors.To identify the impact of social networking activities on corporate image, the dimensions of the two constructs were defined. Utilizing a questionnaire, the perceived importance levels of social networking activities were investigated and the perceptions of the image of corporations actively using social networks were measured. The findings of the research showed that corporations should actively use social networks in order to positively influence their corporate images. To enhance their corporate images and be regarded as industry leading innovative corporations, it is imperative that corporations actively interact with users and provide all the information a user might need in their social networking activities.
Keywords: Corporate Image; Kurum İmajı; Kurumsal İmaj Social Networks; Social Media; Social Media Activities; Social Networking Activities; Sosyal Ağ Aktiviteleri; Sosyal Ağlar; Sosyal Medya; Sosyal Medya Aktiviteleri